Correction: Profound gene expression changes in the epithelial monolayer of active ulcerative colitis and Crohn's disease. - Siri Sæterstad; Ann Elisabet Østvik; Elin Synnøve Røyset; Ingunn Bakke; Arne Kristian Sandvik; Atle van Beelen Granlund (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0265189.].